Pengaruh Kegiatan Menari terhadap Perkembangan Sosial Anak Kelompok B di TK - Dian Ayu Puspita Sari; Nurmala Siregar; Nursyamsiah Simbolon; Hilda Zahra Lubis (CV Edujavare Publishing, 2026)
This study aims to determine the effect of dancing activities on the social development of group B children at Raudhatul Jannah Kindergarten, Medan. Dancing activities are considered as one form of movement art learning that not only trains motor skills, but also forms children's social interaction skills. This study uses a quantitative method with a quasi-experimental design. The subjects of the study were 10 group B children who were selected purposively. Data collection techniques used observation and documentation. The results of the study showed that dancing activities had a positive effect on children's social development, especially in aspects of cooperation, communication, and empathy. Recommendations are addressed to teachers so that movement art activities such as dancing are included in routine activities as a means of forming the social character of early childhood children.